1990
DOI: 10.1139/m90-101
|View full text |Cite
|
Sign up to set email alerts
|

NMR study of 13CO2 incorporation into short-chain fatty acids by pig large-intestinal flora

Abstract: The nuclear magnetic resonance technique was used to study carbon dioxide reduction by the pig large-intestinal flora. Washed bacterial cell suspensions were incubated for 6 and 15 h under 13CO2 and H2 as the gas phase and with a buffer containing NaH13CO3 and cellobiose and amino acids (casein hydrolysate) as substrates. Methane was produced in all incubation media. Significant amounts of single- as well as multiple-labelled acetate and butyrate were formed, demonstrating synthesis of acetate from H2 + CO2. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Subsequent studies on ecosystems such as sewage and anoxic lake sediments showed that several different genera of prokaryotes produce acetate from carbon dioxide [see reviews by Ljungdahl (1986) ;Dolfing (1988) and Wood and Ljungdahl (1990)l. This pathway has also been demonstrated in the gastrointestinal tract of certain animals and humans with the use of labelled CO, (Prins and Lankhorst 1977;Breznak and Switzer 1986;Lajoie et al 1988;De Graeve et al 1990) and suggested stoichiometry (Wolin and Miller 1983;Duncan and Henderson 1990;Demeyer and De Graeve 1991).…”
Section: Introductionmentioning
confidence: 88%
“…Subsequent studies on ecosystems such as sewage and anoxic lake sediments showed that several different genera of prokaryotes produce acetate from carbon dioxide [see reviews by Ljungdahl (1986) ;Dolfing (1988) and Wood and Ljungdahl (1990)l. This pathway has also been demonstrated in the gastrointestinal tract of certain animals and humans with the use of labelled CO, (Prins and Lankhorst 1977;Breznak and Switzer 1986;Lajoie et al 1988;De Graeve et al 1990) and suggested stoichiometry (Wolin and Miller 1983;Duncan and Henderson 1990;Demeyer and De Graeve 1991).…”
Section: Introductionmentioning
confidence: 88%
“…Indeed, a n inverse relation between bacterial numbers responsible for RA and M has been observed i n termite caeca (Brauman et al, 1992) and human and r a t faecal material (Lajoie et al, 1988;Gibson et al, 1990), although RA and M can occur simultaneously De Graeve et al, 1990).…”
Section: A3 Competition and Similarity Between M And Ramentioning
confidence: 99%
“…The stoichiometry used previously may not always be appropriate for the large bowel since work @ith LI contents from rodents (Prins & Lankhorst, 1977), pigs (De Graeve et al 1990) and man (Lajoie et al 1988;Gibson et al 1990) has shown that acetogenesis, i.e. the synthesis of acetate from carbon dioxide and hydrogen may occur in some circumstances.…”
Section: E N E R G Y S a L V A G E By Nsp F E R M E N T A T I O Nmentioning
confidence: 99%